Systematic literature review of Brazilian research on multivariate control charts - Ueda, Renan Mitsuo; da Rosa, Leandro Cantorski; da Silva, Wesley Vieira; Agostino, Ícaro Romolo Sousa; Souza, Adriano Mendonça (Revista Gestão da Produção Operações e Sistemas, 2021)
Purpose – This paper aims to present a Systematic Literature Review (SLR) of studies in Brazil with applications of multivariate control charts indexed in journals on the Web of Science. Design/methodology/approach – The following steps were carried out: a detailed synthesis was performed on the general characteristics of the corpus, co-citation and collaboration networks analyzed; and a co-occurrence of terms in the text corpus was verified. A Systematic Literature Review was carried out using the protocols set out by Biolchini et al. (2007), Kitchenham (2004) and Tranfield, Denyer and Smart (2003). Papers were selected from the Web of Science database, and after applying filters, results for 29 articles were given to compose the corpus. Findings – A tendency was found for an increase in publications, along with more international research on the issue. The journal most used for publication was the Microchemical Journal. This analysis provided relevant authors for research in this area: Harold Hotelling, Douglas Montgomery, and John Frederick MacGregor. Important Brazilian researchers were highlighted who work mainly in the pharmaceutical and biodiesel industry. Originality/value – No articles were found that had carried out a Systematic Literature Review of Brazilian research on multivariate control charts. The main contributions to this manuscript related to an increase in scientific know-how in the area of multivariate and bibliometric analysis. Keywords - Multivariate Control Charts. Systematic literature review. Bibliometric analysis.